Analisis Pemborosan dengan Metode Waste Assessment Model (WAM) dan Fuzzy-Failure Mode Effect Analysis (F-FMEA) di CV. XYZ - Muhammad Mahfudh Bil Haqqi; Enny Aryanny (Universitas Batanghari Jambi, 2026)
This research aims to determine the level of waste that occurs and provide suggestions for improvements to reduce waste at CV XYZ. This research uses primary data obtained in direct research starting from January - April 2024. The data used is questionnaire data with superior respondents who know the real conditions of modified container production and waste data that occurs in the production process. To determine the level of waste that occurs and provide suggestions for improvements to reduce waste, the Waste Assessment Model, Process Activity Mapping, Root Cause Analysis and Fuzzy Failure Mode Effect Analysis methods are used. Using the Waste Assessment Model method, the top three most critical wastes were found, namely defect defects of 25.14%, motion waste of 20.62%, inventory waste of 16.32%. In Root Cause Analysis, the root cause of all waste problems is found by asking why, successively getting to the root of the problem. In the Fuzzy Failure Mode Effect Analysis, the Fuzzy Risk Priority Number value of the top three wastes with each subwaste, waste inventory causing lack of attention to warehouse management, was 6.7, waste defect causing the spray machine not functioning perfectly was 4.95, waste inventory the cause of workers not being orderly with the SOP for recording inventory balances was 4.39, waste motion caused tools to be often moved to reach certain angles was 3.64, waste defect of workers not being careful when setting up was 2.45.